Pelaksanaan Pemungutan Retribusi Terminal di Kabupaten Sukoharjo - Rezi Budiningtyas Ambarwati; Waluyo Waluyo (Jurnal Discretie, 2020)
This Research Aims To Determine The Implementation Of The Collection Of Type C Terminal Levies In Sukoharjo Regency As Well As The Supporting And Inhibiting Factors In The Implementation Of Type C Terminal Levies Collection In Sukoharjo Regency. This Research Was A Normative Or Doctrinal Legal Research With A Statutory Approach And A Conceptual Approach. The Type Of Data Used Is Primary Data And Secondary Data. The Techniques Used In Gathering Legal Materials In This Research Was Interviews And Literature Studies Or Documents. This Research Uses Analytic Syllogism Method Of Deductive Thinking. The Results Of This Reasearch That The Implementation Of Terminal Cost Collection Is In Accordance With Existing Regulations, But There Are Some Obstacles That Cause Terminal Costs Do Not Match The Expected Target.